Chronic hearing loss turns out being a calcified chondroid mesenchymal neoplasm with FN1::FGFR2 fusion - Bauerschmitz, Leonard; Agaimy, Abbas; Eckstein, Markus; Balk, Matthias; Iro, Heinrich; Schleder, Stephan; Schlaffer, Sven-Martin; Gostian, Antoniu-Oreste (European Archives of Oto-Rhino-Laryngology, 2024)
A 53 year old female presented with a six-year history of right-sided slow deterioration in hearing and a feeling of pressure in the right ear. The patient had not experienced any pain but reported some paresthesia of the right half of the tongue, whereas no further other cranial nerve deficits were evident. The otoscopy was unremarkable as well as the rest of the clinical ENT examination except for a slight asymptomatic swelling of the right cheek. Imaging findings showed an expansive tumor infiltrating and destroying the right lateral skull base. The tumor was partially composed of cystic/regressive lesions with high contrast media uptake. The tumor had high-signal intensity with water-sensitive sequences (T2w) and was hypointense on T1w images. We performed a tumor resection via a transparotideal-infratemporal approach. Histologically, the tumor was composed of granular variably calcified chondroid matrix with extensive regressive changes and granulation-like tissue reaction associated with calcinosis and crystal deposition. Molecular analysis of the tumor via the TruSight- RNA-Fusion panel detected a fusion involving FN1::FGFR2, consistent with “calcified chondroid mesenchymal neoplasm” (CCMN), a rare tumor entity recently defined by Liu et al 2021. In regular follow-up care no residual tumor has been detected in imaging studies (MRI and CT) within 2 years and 4 months. The biology and consequently the radio sensitivity cannot be defined precisely since long term results are missing due to the first description of this entity in 2021. As a consequence, surgical resection is recommended as the treatment of choice. Thorough clinical and radiological follow-up is mandatory as local recurrences are to be expected due to the infiltrative behavior. In case of a loco regional recurrence the fusion with FGFR2 may represent a therapeutic option for a targeted therapy on molecular level.
CRIS-Team Scopus Importer:2024-11-01
Keywords: Calcified chondroid mesenchymal neoplasm; Calcifying aponeurotic fibroma; CCMN; Chondrobastoma; Chondroma; Chondrosarcoma; Chordoma; FGF23; FGFR1; FGFR2; FN1; Ossifying fibromyxoid tumor; Phosphaturic mesenchymal tumors; PMT; Skull base tumor; TEK; Temporomandibular Joint; Tenosynovial giant cell tumor; TruSight-RNA-Fusion panel